The Greun System in Lamaholot Customary Marriage: A Maslahah Mursalah Perspective in Islamic Family Law - Zainal Jamin; Kasuwi Saiban; Faishal Agil Al Munawar; Abdurrahman Muhammad Mushab (Institut Agama Islam Negeri Kendari, 2026)
The greun system is a customary mechanism used by the Lamaholot people in regulating marriage based on kinship relations and tribal structure. In practice, greun is often used as the main reference before marriage takes place, even preceding religious considerations. This study addresses the gap in integrating local customary marriage practices with the framework of maṣlaḥah mursalah in Islamic legal theory. This article aims to examine the greun system through the maṣlaḥah mursalah approach in order to assess the legitimacy and limits of its applicability in Islamic marriage law. This research uses a qualitative method with a normative-empirical approach, through the analysis of the literature on fiqh proposals and interviews with traditional and religious leaders in Leworaja Village, Lembata Regency. The results of the study show that greun functions as a customary norm that regulates the selection of mates and maintains social order in the Lamaholot community. Maṣlaḥah Mursalah provides a methodological framework for judging Greun as 'urf which is judged on the basis of maqāṣid al-Syarī'ah. Greun is at the level of maṣlaḥah ḥājiyyāt so that it acts as a mechanism of social benefit without having the authority to determine halal-haram or the legality of marriage according to shari'i. This article contributes to affirming the distinction between customary and sharia authorities and enriching the study of fiqh proposals based on local contexts. Keywords: customary marriage; greun; islamic family law; maṣlaḥah mursalah; ‘urf.